2012
DOI: 10.1371/journal.pone.0047059
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Body Fat Distribution, Epicardial Fat and Obstructive Sleep Apnea in Obese Patients with and without Metabolic Syndrome

Abstract: BackgroundObstructive sleep apnea (OSA) and metabolic syndrome, both closely related to obesity, often coexist in affected individuals; however, body mass index is not an accurate indicator of body fat and thus is not a good predictor of OSA and other comorbidities. The aim of this study was to investigate whether the occurrence of OSA could be associated with an altered body fat distribution and a more evident cardio metabolic risk independently from obesity and metabolic syndrome.Methods and Results171 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 56 publications
3
35
0
4
Order By: Relevance
“…There are limited data on the association between EAT and OSAHS. Two previous studies demonstrated a possible association between EAT thickness and OSAHS severity in obese patients [18] and in OSAHS patients with and without metabolic syndrome [19]. Another study was found thicker EAT only in women with severe OSAHS [20].…”
Section: Introductionmentioning
confidence: 90%
“…There are limited data on the association between EAT and OSAHS. Two previous studies demonstrated a possible association between EAT thickness and OSAHS severity in obese patients [18] and in OSAHS patients with and without metabolic syndrome [19]. Another study was found thicker EAT only in women with severe OSAHS [20].…”
Section: Introductionmentioning
confidence: 90%
“…A obesidade geral e, principalmente, a abdominal contribuem como principais fatores determinantes de hipoventilação e, além disso, colaboram para o aparecimento da apneia obstrutiva que aumenta o colapso das vias aéreas superiores [4][5][6] . Portanto, devido à grande importância da avaliação da gordura abdominal, torna-se necessário realizar a antropometria para a sua detecção.…”
Section: N T R O D U ç ã Ounclassified
“…Lubrano et al 6 também encontraram um percentual de SM maior entre os pacientes com a síndrome (65,4%), porém, diferente desta pesquisa, a prevalência da SM estava aumentada em função da gravidade da SAOS: 52,4% dos pacientes com SAOS leve, 69,2% dos com SAOS moderada e 77,8% dos com SAOS grave. Embora a relação da SAOS com a SM tenha sido amplamente atribuída à obesidade, os mecanismos exatos da associação entre a síndrome e suas características individuais ainda permanecem não elucidados 14 .…”
Section: I S C U S S ã Ounclassified
See 1 more Smart Citation
“…Childhood and adult obesity are two of the most critical threats to health in recent decades [2,3]. Obesity is caused by several factors, and its pathogenesis involves interplay of social, genetic and environmental considerations [4].…”
Section: Introductionmentioning
confidence: 99%